Blue giant [videorecording (Blu-Ray)] (Shout! Factory, 2024)
Dai Miyamoto's life is turned upside down the day he discovers jazz. A former high school basketball player, Dai picks up a saxophone and begins practicing day and night, determined to become one of the greatest of all time. He leaves his sleepy hometown for the bustling nightclubs of Tokyo but soon finds the life of a professional musician is not for the faint of heart. His passion eventually wins over the cocky but talented pianist Yukinori, and after Dai convinces his friend Shunji to learn the drums, they launch a new jazz trio whose rough sound contains a raw energy that quickly wins the attention of local audiences. But what does it take to truly be great?